2018
DOI: 10.2337/dc17-0662
|View full text |Cite
|
Sign up to set email alerts
|

Time to Treatment Intensification After Monotherapy Failure and Its Association With Subsequent Glycemic Control Among 93,515 Patients With Type 2 Diabetes

Abstract: Earlier treatment intensification is associated with shorter time to subsequent glycemic control, independent of whether patients initiate first-line treatment with metformin or a sulfonylurea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 26 publications
2
40
1
2
Order By: Relevance
“…Numerous studies have established that after treatment intensification, delays have been shown to be associated with poorer response to the added therapy. Thus, delaying treatment intensification exposes patients to avoidable hyperglycaemia both during and after the delays . These results highlight the benefit of early initiation of intensification therapy in patients not at target, and demonstrate that prolonged hyperglycaemia may be associated with decreased ability to reach target.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Numerous studies have established that after treatment intensification, delays have been shown to be associated with poorer response to the added therapy. Thus, delaying treatment intensification exposes patients to avoidable hyperglycaemia both during and after the delays . These results highlight the benefit of early initiation of intensification therapy in patients not at target, and demonstrate that prolonged hyperglycaemia may be associated with decreased ability to reach target.…”
Section: Discussionmentioning
confidence: 77%
“…Thus, delaying treatment intensification exposes patients to avoidable hyperglycaemia both during and after the delays. [14][15][16][17] These results highlight the benefit of early initiation of intensification therapy in patients not at target, and demonstrate that prolonged hyperglycaemia may be associated with decreased ability to reach target.…”
Section: Discussionmentioning
confidence: 79%
“…This stepped‐care approach can substantially delay HbA1c goal attainment in patients who ultimately require two or more AHAs for optimal glycaemic control. A recent analysis of observational data in the United Kingdom indicated that only 25% of patients with T2D with HbA1c ≥53 mmol/mol (≥7.0%) received treatment intensification within 12 months . Further, the likelihood of attaining glycaemic control was significantly lower for patients with delayed intensification.…”
Section: Introductionmentioning
confidence: 99%
“…Delays in anti‐hyperglycaemic treatment intensification (TI) are common and often result in exposure to unnecessarily high levels of A1C that can last for months or even years . Following TI, these delays have been shown to be associated with poorer response to the additional therapy . Thus, delaying TI exposes patients to avoidable hyperglycaemia, both during and after the delays.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Following TI, these delays have been shown to be associated with poorer response to the additional therapy. [5][6][7][8] Thus, delaying TI exposes patients to avoidable hyperglycaemia, both during and after the delays. There are many reasons why patients and their clinicians do not intensify therapy in a timely manner, including fear of insulin (needle anxiety), 9 competing demands at clinical encounters, 10 polypharmacy, 11 costs and costsharing issues, 12,13 health system barriers, 13 and clinical inertia.…”
Section: Introductionmentioning
confidence: 99%